Risk factors for Salmonella Dublin on dairy farms in Ontario, Canada - K.V. Perry; D.F. Kelton; S. Dufour; C. Miltenburg; S.G. Umana Sedo; D.L. Renaud (Journal of Dairy Science, 2023)
ABSTRACT: Salmonella Dublin is an emerging pathogen on dairy farms in Canada. In Ontario, Salmonella Dublin has been increasingly isolated from diagnostic laboratory samples. The objective of this observational cross-sectional study was to identify management practices associated with herd positivity for Salmonella Dublin. A convenience sample of 100 dairy farms was visited in Ontario, Canada, from April to August 2022. Farms were visited once to collect blood samples from 20 heifers between 4 and 24 mo old, sample bulk tank milk, and administer an in-person questionnaire on management practices. An additional bulk tank milk sample was collected before the visit by milk transporters. All bulk tank and serum samples underwent ELISA testing to determine Salmonella Dublin positivity (≥35% positivity on ELISA). Of the 1,990 heifers sampled, 44 (2.2%) animals were seropositive for Salmonella Dublin. At least one seropositive heifer was identified on 24% of participating farms. Based on the bulk tank milk samples collected during both sampling periods, 4% of farms were positive for Salmonella Dublin. Overall, of the 100 farms visited, 25% were classified as Salmonella Dublin positive, meaning at least one serum or bulk tank sample was interpreted as positive. A multivariable logistic regression model identified 5 factors associated with herd-level positivity for Salmonella Dublin. Specifically, introducing purchased animals within the last 2 years increased the likelihood that farms were positive for Salmonella Dublin (odds ratio [OR] = 4.6). Farms that had at least one animal leave the premises for a cattle show, embryo collection center, or loan to another farm and return within the last 2 years were also at a higher risk for Salmonella Dublin (OR = 4.9). Farms that removed manure from the surface of bedding in calving pens twice per month or after every calving were at greater risk for Salmonella Dublin than farms that removed manure less frequently (OR = 8.5). Farms that added bedding material to calving areas once or twice weekly were at lower risk for Salmonella Dublin compared with farms that added bedding less than once weekly (OR = 0.1). In addition, farms that kept 3 cows or less per pen in the calving area were at lower risk for Salmonella Dublin. Test positivity for Salmonella Dublin among Ontario dairy farms sampled is high, and dairy producers should consider avoiding management practices that are associated with an increased risk of Salmonella Dublin infection.